International Humanitarian Law in Areas of Limited Statehood Adaptable and Legitimate or Rigid and Unreasonable? - Petrov, Anton O.; Mührel, Linus; Baade, Björnstjern (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
Areas of limited statehood, in which the territorial State lacks effective control, either completely or in part, challenge International Humanitarian Law in various ways. This volume explores if and how the law adapts to these challenges on the basis of mainly two legal issues: detention and investment protection in (non-)international armed conflict. Does a sufficient legal basis exist for the former? Is it International Humanitarian Law that determines what the investor is owed under a 'full protection and security' standard?More fundamentally, the contributions strive to shed light on these practical legal issues in a manner that is also historically and theoretically informed. How can international law be effective in areas of limited statehood, in particular as regards non-State actors? Can the law provide incentives for compliance? Is it in need of being developed? If so, who enjoys the legitimacy to do so?